Hypovitaminosis D and linkages to sleep and fatigue in Turkish patients with and without rheumatoid arthritis: The implications of stopping vitamin D testing - Celenk, Onur; Mercan Baspinar, Melike; Esatoglu, Sinem Nihal; Basat, Okcan (Journal of Surgery and Medicine, 2025)
Background/Aim: We investigated Vitamin D levels in Turkish patients with and without rheumatoid arthritis (RA) to examine relationships with disease activity, sleep quality, sleepiness, fatigue, and physical capacity. Additionally, we evaluated the broader implications of the recent withdrawal of vitamin D testing from primary care settings. Methods: A single-center, analytical study was conducted using laboratory records and various questionnaires: the Health Assessment Questionnaire (HAQ), Disease Activity Score (DAS-28), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Fatigue Severity Scale (FSS), Visual Analogue Scale (VAS) for pain, and Physical Activity Questionnaire for Primary Care (PAQ-PC). Results: A total of 192 patients were evaluated, including106 with RA that had a mean age of 53.5 (14.2) years; we also studied 86 controls that had a mean age of 49.8 (13.4) years with similar Vitamin D levels (21.02 [10.78] ng/mL vs 20.22 [8.81]) ng/mL; P=0.578). The prevalence of hypovitaminosis D was also similar across the groups (52.8% vs 48.8%; P=0.578). The Vitamin D levels of the RA patients were negatively correlated with pain (r=-0.286; P=0.033), tender joint count (r=-0.197 P=0.042), and disease activity (r=-0.286 P=0.003). In addition, RA patients exhibited poorer sleep quality and more daytime sleepiness compared with the controls; the RA patients had significantly poorer sleep quality scores (P<0.001). Similarly, the control group with hypovitaminosis D were found to have higher levels of fatigue and daytime sleepiness compared with individuals with normal Vitamin D levels (P=0.035 and P=0.019, respectively). Conclusion: Given the high prevalence of hypovitaminosis D and its associations with disease activity, pain, fatigue, and poor sleep in patients with RA, these findings highlight the need to reconsider routine vitamin D screening in primary care, particularly for vulnerable and chronically ill populations.